INVESTIGATION OF THE POSSIBILITY OF USING A VORTEX HEAT GENERATOR IN HEAT SUPPLY SYSTEMS FOR RESIDENTIAL, INDUSTRIAL AND PUBLIC BUILDINGS - I. L. Iokova; E. N. Tarasevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In a number of foreign countries, vortex heat generators have become widespread in decentralized heat supply systems. For Belarus, vortex heat generators are quite new sources of heat supply. The article considers the possibility of using vortex heat generators for heat supply systems for residential, public and industrial buildings. Vortex heat generators are based on the principle of cavitation in a turbulent water flow. For many devices cavitation is not desirable, but in a vortex heat generator it is used as a favorable phenomenon. The authors carried out a series of full-scale experiments to determine the efficiency of the “VTG-2.2” vortex heat generator when different operating modes were applied. The performance of the vortex heat generator can be estimated by the energy conversion factor. Energy conversion factor is the ratio of the amount of thermal energy that a vortex heat generator generates to the amount of electrical energy consumed. Experiments conducted in a number of research organizations (including the National Academy of Sciences of Ukraine and MPEI) have demonstrated that energy conversion factor can exceed 1. The authors conducted experimental tests with the use of an experimental installation simulating a heat supply system. According to the obtained experimental data, the energy conversion coefficients for each mode were calculated. The constructed graphical dependencies clearly demonstrate that, with increasing rotational speed of the vortex heat generator, the efficiency of its use increases. The highest energy conversion factor value was 61.1 % with a rotation frequency of 40 Hz. It was also found that with increasing the rotational speed of the vortex heat generator, a significant increase in noise and vibration occurs.